Family dental health care service - Wardani, Riana (Universitas Padjadjaran, 2008)
The Family Dental Health Care Service is a new approach that includes efforts to serve oral and dental patients that focuses on maintenance, improvement and protection. This oral and dental health approach uses basic dentistry science and technology. The vision of the Family Dental Health Care Service is the family independences in the effort of dental health maintenance and to achieve the highest oral and dental health degree as possible through family dentist care that is efficient, effective, fair, evenly distributed, safe and has a good quality. To support this effort, the Ministry of Health has issued Health Care Policy and Implementation Guideline as well as the licensing standard for family dentist practice.